Numerical modelling of tidal sediment dynamics in the Bay of Brest over the Holocene: How the use of a process-based model over paleoenvironmental reconstitutions can help understand long-term tidal deposits?. (31st May 2023) - Olivier, Matthieu Guillaume; Leroux, Estelle; Granjeon, Didier; Le Hir, Pierre; Rabineau, Marina; Le Roy, Pascal; Simplet, Laure; Ehrhold, Axel; Muller, Héloïse
Abstract: Long-term sedimentary infill of tide-dominated estuaries remains poorly understood. The main issue is the time-scale gap between the tidal process (hourly variations) and sedimentary layer formation (hundreds to thousands of years). Hydrodynamics induced by tides are responsible for intense remobilization of sedimentary layers inside estuaries and thus only partial sedimentary records are available. This consequently complicates understanding and interpreting the influence of hydrodynamic forcings via the preserved sedimentary deposits, as well as their chronology. Numerical modelling would appear to be the most-appropriate solution to overcome the lack of sediment deposit preservation. Hydro-sediment modelling explicitly simulates the impact of tidal processes on sediments. However, simulations time-span of these models are currently limited to decades, without simplification or schematization of the tide impact on sediments. This study (and Olivier et al., 2021) exposes a methodology exploring the evolution of sediment dynamics induced by tide over large time-scales ( e.g. a transgression, ∼10 ka). The aim is to use sedimentary records to identify and rebuild each key paleoenvironments of the sediment infilling in a tide-dominated estuary (defined as seafloor morphology and sea-level), in order to run them through hydro-sedimentary simulations (MARS3D/MUSTANG). The Bay of Brest is the area selected to test the methodology. Four paleoenvironments defined by distinct sea-level and seafloor scenarios are used to study the evolution of tidal-current impact on the erosion/deposition patterns over the last 9000 years. Simulation results were compared with sedimentary records in terms of: sedimentation rates, distribution of erosion/deposition patterns (as deduced from seismic records) and distribution of grain-size classes (comparison with cores). Simulation results allowed to: (I) explain most of the sediment distribution for each sedimentary unit, reconstruct tide influence on the Holocene infilling of the Bay of Brest over 9 ka; (II) discuss the evolution of the influence of sediment supply sources; (III) highlight the spatial evolution of erosion and deposition, and the limit between cohesive and non-cohesive deposits, which evolve with tidal prism increase in relation to the active-flow section width in the Bay of Brest: when fast and significant expansion of the active-flow section width occurs ( e.g. inundation of extended terraces becoming subtidal) those boundaries move down-estuary, while the opposite occurs when the increase of active-flow section width remains low during sea-level rise. Highlights: Set up of a methodology to explore the impact of tides on sedimentation over 9 ka. Tide-induced sedimentation is reconstructed over the Holocene in the Bay of Brest. Most of the sediment deposits in the Bay of Brest are supplied by oceanic borders. Sandy/muddy deposition limit varies with the tidal prism/active flow section ratio.